Contributing role of extracellular vesicles on vascular endothelium haemostatic balance in cancer - Bouvy, Céline (Co-Action Publishing, 2014)
Extracellular vesicles (EVs) generated during tumourigenesis are thought to play a major role in the hypercoagulant state observed in cancer patients. They exhibit negatively charged phospholipids and tissue factor (TF) that promote coagulation cascade activation. In addition, they contain surface proteins and cytoplasmic molecules, both originating from the producing cell that can impact target cells’ expression. By targeting endothelial cells of blood vessels, these EVs could disturb the physiological anticoagulant properties of these cells and be partly responsible for the vascular endothelium activation observed in cancer patients. Indeed, vascular endothelium naturally exhibits heparin-like proteoglycan, TF pathway inhibitor and protein C anticoagulant pathway that prevent thrombosis in physiological condition. An overexpression of TF and a decreased expression of coagulation cascade inhibitors have been reported after EVs’ treatment of endothelial cells. The induction of apoptosis and an increased expression of platelet adhesion molecules have also been highlighted. These events may promote thrombus formation in cancer. The aim of this paper is to provide a targeted review on the current evidence and knowledge of roles and impact of EVs on endothelial surface anticoagulant and procoagulant factors and cellular adhesion molecules expression.